Decidualisation of human endometrial stromal cells is associated with increased expression and secretion of prorenin. Issue 1 (December 2015) - Lumbers, Eugenie; Wang, Yu; Delforce, Sarah; Corbisier de Meaultsart, Celine; Logan, Philip; Mitchell, Murray; Pringle, Kirsty
Abstract Background In pregnancy, the decidualised endometrium expresses high levels of prorenin and other genes of the renin-angiotensin system (RAS) pathway. In this study we aimed to determined if the RAS was present in endometrial stromal cells and if decidualisation upregulated the expression of prorenin, the prorenin receptor ((P)RR) and associated RAS pathways. Immortalised human endometrial stromal cells (HESCs) can be stimulated to decidualise by combined treatment with medroxyprogesterone acetate (MPA), 17β-estradiol (E2 ) and cAMP (MPA-mix) or with 5-aza-2'-deoxycytidine (AZA), a global demethylating agent. Methods HESCs were incubated for 10 days with one of the following treatments: vehicle, MPA-mix, a combination of medroxyprogesterone acetate (MPA) and estradiol-17β alone, or AZA. Messenger RNA abundance and protein levels of prorenin (REN ), the (P)RR (ATP6AP2 ), angiotensinogen (AGT ), angiotensin converting enzyme (ACE ), angiotensin II type 1 receptor (AGTR1 ), vascular endothelial growth factor (VEGF), and plasminogen activator inhibitor-1 (PAI-1) were measured by real-time PCR and ELISA's, respectively. Promyelocytic zinc finger (PLZF ) and phospho-inositol-3 kinase (PIK3R1 ) mRNA abundances were also measured. Results HESCs expressed the prorenin receptor (ATP6AP2 ), REN, AGT, ACE and low levels ofAGTR1 . MPA-mix and AZA stimulated expression ofREN . Prorenin protein secretion was increased in MPA-mix treated HESCs. E2 + MPA had no effect on any RAS genes. MPA-mix treatment was associated with increased VEGF (VEGFA ) and PAI-1 (SERPINE1 ) mRNA and VEGF protein. Conclusions An endometrial prorenin receptor/renin angiotensin system is activated by decidualisation. Since (P)RR is abundant, the increase in prorenin secretion could have stimulatedVEGF A andSERPINE1 expression via Ang II, as bothACE andAGTR1 are present, or by Ang II independent pathways. Activation of the RAS in human endometrium with decidualisation, through stimulation of VEGF expression and secretion, could be critical in establishing an adequate blood supply to the developing maternal placental vascular bed.